Inovação tecnológica na indústria automobilística: características e evolução recente - Carvalho, Enéas Gonçalves de [UNESP] (Universidade Estadual de Campinas (UNICAMP), Instituto de Economia, 2008)
O objetivo principal deste artigo é analisar as características básicas da evolução recente do processo de inovação tecnológica na indústria automobilística. A hipótese de trabalho é que estariam ocorrendo mudanças na intensidade do processo de inovação técnica nessa indústria. O ponto de partida é a observação de que, nos últimos anos, tem havido na indústria automotiva - provavelmente em decorrência da intensificação da concorrência setorial e de uma maior oportunidade tecnológica - tanto uma ampliação dos gastos em P&D quanto uma crescente incorporação da microeletrônica (nos produtos e nos processos produtivos). Finalmente, são feitas também algumas considerações procurando relacionar os resultados obtidos neste artigo com a discussão do processo de de-maturity (rejuvenescimento) industrial, proposto por Abernathy e outros autores.

The main goal of this article is to analyze the recent evolution of the technological innovation process in the automobile industry. A provisional assumption is that could be happened changes on the auto industry technical innovation process. The starting point is the observation that, in the last years, there have been both - probably as consequence of the sectorial competition intensification and the higher technological opportunity - an amplification of the expenses in R&D as well as an increasing incorporation of the microelectronics, in the products and in the productive processes, by the automobile industry. Finally, some considerations are made, aiming at relating the obtained results in this article with the discussion of the de-maturity industrial process proposed by Abernathy and other authors.
Technological innovation in the automotive industry: features and recent evolution
Keywords: Brasil; Inovação tecnológica; Empresas multinacionais; Competitividade internacional; Brazil; Technological innovation; Multinational firms; International competitiveness